10 | − | x | = | 1 | ÷ | 3 | × | ( | 10 | − | 1 | ÷ | 2 | × | x | ) |
Right side of the equation = | 1 3 | ( | 10 | − | 1 | ÷ | 2 | × | x | ) |
10 | − | x | = | 1 3 | ( | 10 | − | 1 | ÷ | 2 | × | x | ) |
Right side of the equation = | 1 3 | × | 10 | − | 1 3 | × | 1 | ÷ | 2 | × | x |
= | 10 3 | − | 1 6 | x |
10 | − | x | = | 10 3 | − | 1 6 | x |
- | x | + | 1 6 | x | = | 10 3 | − | 10 |
- | 5 6 | x | = | 10 3 | − | 10 |
- | 5 6 | x | = | - | 20 3 |
20 3 | = | 5 6 | x |
5 6 | x | = | 20 3 |
x | = | 20 3 | ÷ | 5 6 |
= | 20 3 | × | 6 5 |
= | 4 | × | 2 |
x | = | 8 |